Classification of phytoplankton cells as live or dead using the vital stains fluorescein diacetate and 5-chloromethylfluorescein diacetate - MacIntyre, Hugh L (Journal of phycology, 2016)
© 2016 The Authors. Journal of Phycology published by Wiley Periodicals, Inc. on behalf of Phycological Society of America.